2003
DOI: 10.1016/s0048-7333(02)00137-3
|View full text |Cite
|
Sign up to set email alerts
|

Measuring innovative performance: is there an advantage in using multiple indicators?

Abstract: The innovative performance of companies has been studied quite extensively and for a long period of time. However, the results of many studies have not yet led to a generally accepted indicator of innovative performance or a common set of indicators. So far the variety in terms of constructs, measurements, samples, industries and countries has been substantial. This paper studies the innovative performance of a large international sample of nearly 1200 companies in four high-tech industries, using a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
669
1
52

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,187 publications
(736 citation statements)
references
References 56 publications
14
669
1
52
Order By: Relevance
“…The methodology used is based on prior research measuring the innovation performance based on the number of patents (Hagedoorn and Schakenraad 1994;Henderson and Cockburn 1994;Ahuja 2000;Stuart 2000;Owen-Smith and Powell 2004;Rothaermel and Hess 2007;Rothaermel and Thursby 2007;Rothaermel and Alexandre 2009). Patent count is not only a typical method for measuring technological innovation but is also highly correlated with other indicators of firm innovativeness, such as the number of new product introductions (Hagedoorn and Cloodt 2003). In particular, we measure the technology innovation performance of firms by the number of Korean patents applied for from 2008 to 2010.…”
Section: Dependent Variablementioning
confidence: 99%
“…The methodology used is based on prior research measuring the innovation performance based on the number of patents (Hagedoorn and Schakenraad 1994;Henderson and Cockburn 1994;Ahuja 2000;Stuart 2000;Owen-Smith and Powell 2004;Rothaermel and Hess 2007;Rothaermel and Thursby 2007;Rothaermel and Alexandre 2009). Patent count is not only a typical method for measuring technological innovation but is also highly correlated with other indicators of firm innovativeness, such as the number of new product introductions (Hagedoorn and Cloodt 2003). In particular, we measure the technology innovation performance of firms by the number of Korean patents applied for from 2008 to 2010.…”
Section: Dependent Variablementioning
confidence: 99%
“…With respect to high-tech companies, Hagedoorn and Cloodt (2003) discuss the absence of a generally accepted metric of innovation despite the long tradition of using single metrics to study innovation, including R&D, patents, and new product announcements,. In response they propose a composite innovation metric to describe companies' overall 'innovative performance'…”
Section: Lack Of Integrated Metrics For Energy Technology Innovationmentioning
confidence: 99%
“…A clear advantage of this measurement of innovative outcomes is that it captures the confrontation of the (product) innovation with the demands of the market and thus is more close to the general accepted definition of innovation that includes the market introduction of the innovation (Hagedoorn and Cloodt 2003).…”
Section: Firm Innovativenessmentioning
confidence: 99%
“…Firms are asked whether they introduced new or improved products, services or processes during the two previous years for each of the categories of newness presented in the above. Research has shown that these subjective indicators are just as valid as measures of innovative performance as the more objective indicators mentioned in the above (Hagedoorn and Cloodt 2003).…”
Section: Firm Innovativenessmentioning
confidence: 99%